Reorganisation of rhizosphere soil pore structure by wild plant species in compacted soils. (15th July 2020) - Burr-Hersey, Jasmine E; Ritz, Karl; Bengough, Glyn A; Mooney, Sacha J
Abstract : Soil porosity is increased within the rhizosphere of three common wild plant species growing in compacted soil, with significant differences between species. Abstract: Soil compaction represents a major impediment to plant growth, yet wild plants are often observed thriving in soil of high bulk density in non-agricultural settings. We analysed the root growth of three non-cultivated species often found growing in compacted soils in the natural environment. Plants of ribwort plantain ( Plantago lanceolata ), dandelion ( Taraxacum officinale ), and spear thistle ( Cirsium vulgare ) were grown for 28 d in a sandy loam soil compacted to 1.8 g cm –3 with a penetration resistance of 1.55 MPa. X-Ray computed tomography was used to observe root architecture in situ and to visualise changes in rhizosphere porosity (at a resolution of 35 μm) at 14 d and 28 d after sowing. Porosity of the soil was analysed within four incremental zones up to 420 μm from the root surface. In all species, the porosity of the rhizosphere was greatest closest to the root and decreased with distance from the root surface. There were significant differences in rhizosphere porosity between the three species, with Cirsium plants exhibiting the greatest structural genesis across all rhizosphere zones. This creation of pore space indicates that plants can self-remediate compacted soil via localised structural reorganisation in the rhizosphere, which has potential functional implications for both plant and soil.